Analisis Yuridis Ketentuan Negara Tuan Rumah Dalam Kegiatan Foreign Direct Investment (FDI) Berbentuk Joint Venture - Ayu Sacha Maharani, Ratu (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
In 2023, Indonesia is expected to continue attracting foreign direct investment through joint ventures. The Indonesian government has actively promoted foreign direct investment (FDI) and facilitated Joint Ventures to attract foreign capital and expertise. Foreign Direct Investment (FDI) is a direct investment made by foreign companies in the host country. One common form of FDI is a joint venture, where a foreign company and a local company work together to form a new entity that will operate in the host country. In this context, juridical analysis refers to research and evaluation of the legal provisions applicable in the host country related to FDI activities in the form of joint ventures. This analysis involves understanding the legal regulations governing the formation, operation and termination of joint ventures, as well as the legal protection provided to the parties involved in these activities. Juridical analysis of the host country's provisions for FDI activities in the form of joint ventures is important to understand the applicable legal framework and ensure compliance with existing regulations. This can also help the parties involved in the joint venture to protect their rights and interests and minimize any legal risks that may arise.